Malus taxa and the progenies of Malus floribunda selected in Hungary, as gene sources of resistance breeding - G. Tóth, M.; Kovács, Sz. (International Journal of Horticultural Science, 2004)
One of our objectives in the apple breeding program of the Department of Fruit Science, beside creating new varieties, is to search for new gene sources. After evaluating the disease resistance of Malus taxa available in Hungary, we put the promising selected individuals through further examinations. Their habit and growth vigor was observed, as well as productivity and fruit characteristics were evaluated. Malus fusca seems to be a new, promising gene source in Hungary among the examined taxa. Beside its optimal canopy, growth vigor and fruit characteristics, it has the advantage to be in distant relationship to Malus x domestica, therefore its resistance is based on a different genetic basis. SBG 1 selection of Malus spectabilis can be recommended as a new gene source for resistance breeding. The range of gene sources can further be widened by selected clones of Malus floriblunda (BA I), Malus x zumi (BA) and Malus baccata (SBG 6). An additional value of Malus taxa chosen by us is that they show resistance not only to apple scab, but to powdery mildew as well, and according to our results, they have optimal habit, acceptable productivity and good fruit quality. Nine hybrids were selected from first Malus progenies which proved to be resistant to apple scab and powdery mildew. These are valuable not only as gene sources of breeding, but as pollenizers or ornamental trees, while their decorative fruits can be used in inside decorations and flower arrangements.